Genetic nicotinamide N-methyltransferase (Nnmt) deficiency in male mice improves insulin sensitivity in diet-induced obesity but does not affect glucose tolerance - Brachs, Sebastian; Kannt, Aimo (Diabetes, 2019)
Antisense oligonucleotide knockdown (ASO-KD) of nicotinamide N-methyltransferase (NNMT) in high-fat diet (HFD)–fed mice has been reported to reduce weight gain and plasma insulin levels and to improve glucose tolerance. Using NNMT-ASO-KD or NNMT knockout mice (NNMT−/−), we tested the hypothesis that Nnmt deletion protects against diet-induced obesity and its metabolic consequences in males and females on obesity-inducing diets. We also examined samples from a human weight reduction (WR) study for adipose NNMT (aNNMT) expression and plasma 1-methylnicotinamide (MNAM) levels. In Western diet (WD)–fed female mice, NNMT-ASO-KD reduced body weight, fat mass, and insulin level and improved glucose tolerance. Although NNMT−/− mice fed a standard diet had no obvious phenotype, NNMT−/− males fed an HFD showed strongly improved insulin sensitivity (IS). Furthermore, NNMT−/− females fed a WD showed reduced weight gain, less fat, and lower insulin levels. However, no improved glucose tolerance was observed in NNMT−/− mice. Although NNMT expression in human fat biopsy samples increased during WR, corresponding plasma MNAM levels significantly declined, suggesting that other mechanisms besides aNNMT expression modulate circulating MNAM levels during WR. In summary, upon NNMT deletion or knockdown in males and females fed different obesity-inducing diets, we observed sex- and diet-specific differences in body composition, weight, and glucose tolerance and estimates of IS.